2023
DOI: 10.1002/celc.202300428
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking High‐Performance Supercapacitor Behavior and Sustained Chemical Stability of 2D Metallic CrSe2 by Optimal Electrolyte Selection

Weihao Li,
Niklas Wolff,
Arun Kumar Samuel
et al.

Abstract: Supercapacitors are energy storage devices with the ability to rapidly charge and discharge, making them a valuable complement to battery systems. To maximize their fast‐charging capabilities, identifying materials and methods to enhance their energy density is crucial. In this work, we carried out a comprehensive study of an emerging 2D dichalcogenide, CrSe2, as a supercapacitor material. We demonstrate that CrSe2 can be obtained at ambient temperature through deintercalation of a relevant KCrSe2 precursor us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…The peaks associated with the 1T′-monoclinic phase were still present (Figure S21a) and consistent with the XRD pattern of the sample before the electrolyzer testing. This confirmed that the bulk of the sample did not degrade or convert to other polymorphs, consistent with the behavior of related TMDCs in acidic conditions . However, Raman spectroscopy collected on 1T′-MoTe 2 /CC after galvanostatic electrolysis provided additional information.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The peaks associated with the 1T′-monoclinic phase were still present (Figure S21a) and consistent with the XRD pattern of the sample before the electrolyzer testing. This confirmed that the bulk of the sample did not degrade or convert to other polymorphs, consistent with the behavior of related TMDCs in acidic conditions . However, Raman spectroscopy collected on 1T′-MoTe 2 /CC after galvanostatic electrolysis provided additional information.…”
Section: Resultssupporting
confidence: 77%
“…This confirmed that the bulk of the sample did not degrade or convert to other polymorphs, consistent with the behavior of related TMDCs in acidic conditions. 46 However, Raman spectroscopy collected on 1T′-MoTe 2 /CC after galvanostatic electrolysis provided additional information. The band corresponding to the A g mode of 1T′-MoTe 2 was still observed at ∼160.2 cm –1 , consistent with the results of XRD.…”
Section: Resultsmentioning
confidence: 99%